2008
DOI: 10.1002/pd.2059
|View full text |Cite
|
Sign up to set email alerts
|

Decisional needs assessment regarding Down syndrome prenatal testing: a systematic review of the perceptions of women, their partners and health professionals

Abstract: Interventions regarding a decision about prenatal testing for Down syndrome should address many decisional needs, which may indeed vary among the parties involved, whether women, their partners or health professionals. Very little is known about the decisional needs of partners and health professionals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
1
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(70 citation statements)
references
References 63 publications
3
64
1
2
Order By: Relevance
“…We used a vote-counting method [39] which consists of the count of the significant effect directions by considering the same operational definition of the dependent variable. This method has been previously used in systematic reviews in medicine [40,41,42]. Our review shows that 60% of the categories of variables were considered in studies that integrated RP and RC in a comprehensive process.…”
Section: Resultsmentioning
confidence: 99%
“…We used a vote-counting method [39] which consists of the count of the significant effect directions by considering the same operational definition of the dependent variable. This method has been previously used in systematic reviews in medicine [40,41,42]. Our review shows that 60% of the categories of variables were considered in studies that integrated RP and RC in a comprehensive process.…”
Section: Resultsmentioning
confidence: 99%
“…Research on attitudes towards parenting a child with a disability has found that the perceived lack of rewards associated with parenting an affected child predicts intentions to using prenatal diagnosis (Lawson, 2006). Holding clear views about the acceptability or non-acceptability of the birth of a disabled child has been shown to ease prenatal test decision making (St-Jacques et al, 2008). Qualitative work has also shown that women may talk about their experiences of disabled people and their views on parenting a disabled child when being interviewed about why they accepted or rejected prenatal testing (Etchegary et al, 2008;Leuzinger-Bohleber, Engels, & Tsiantis, 2008;Lewando-Hundt et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the men's participation in decisions concerning amniocentesis, our findings were consistent with those of Kenen et al (2000) where expectant fathers describe this decision as a joint enterprise with their female partner. Nevertheless, very little is known about decisional needs of partners regarding prenatal testing (St-Jacques et al, 2008). However, recent research indicates that men's desire to be more involved in consultations before prenatal screening, both for their own needs prior to becoming fathers, but also to enable them to support their spouse when dealing with difficult issues (Williams et al, in press).…”
Section: The Decision Concerning Amniocentesis or Notmentioning
confidence: 97%